Experimental investigations on three-phase interleaved SAPF with modified indirect current control algorithm. (15th April 2021) - Gali, Vijayakumar; Gupta, Nitin; Gupta, R.A.
This paper presents a novel inverter topology, called three-phase interleaved inverter for three-phase shunt active power filter (SAPF). This proposed topology is used for compensating current harmonics, reactive power to improve the power factor of the system. In addition, it eliminates the shoot-through problem which is the hazardous problem in conventional voltage source inverter (VSI)-based SAPF. This proposed topology uses reference current generation techniques to control the flow of compensating currents and reactive power. The existing feed forward control techniques results in switching notches and distortions in the reference source current, hence, poor harmonic compensation. Modified indirect current control (MICC) technique is implemented in this paper to generate a reference current without distortions. Therefore, no switching notches and ripples present in the source current, hence, the source current %THD will be improved. The proposed system is modelled by using MATLAB®/Simulink software to test its performance. Also, a laboratory prototype has been designed and developed using dSPACE1104 controller to validate the simulation results. The test results show the viability of the control algorithm and performance of the proposed interleaved inverter in power quality applications.